I n = ∫ 0 4 π tan n x d x
We define the integral as above. And define the relation f ( n ) = I n − 2 − I n + 2 1 . Evaluate the summation below.
2 r = 2 ∑ 1 0 f ( r )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great use of reduction formula!
I can't believe how complicated yet beautiful math gets. I just finished my math exams and it seems my skills are just the basics of the basic!!!
Problem Loading...
Note Loading...
Set Loading...
Let's calculate the integral first:- I n = ∫ 0 4 π t a n n x d x I n = ∫ 0 4 π t a n n − 2 x t a n 2 x d x I n = ∫ 0 4 π t a n n − 2 x ( s e c 2 x − 1 ) d x I n = ∫ 0 4 π t a n n − 2 x s e c 2 x d x − ∫ 0 4 π t a n n − 2 x d x I n = [ n − 1 t a n n − 1 x ] 0 4 π − I n − 2 I n + I n − 2 = n − 1 1 … ( 1 ) Now we can write that:- I n + 2 + I n = n + 1 1 … ( 2 ) Subtracting ( 2 ) from ( 1 ) . I n − 2 − I n + 2 = n − 1 1 − n + 1 1 f ( n ) 1 = n 2 − 1 2 f ( n ) = 2 n 2 − 1 Now we can find the sum. 2 r = 2 ∑ 1 0 f ( r ) = 2 r = 2 ∑ 1 0 2 r 2 − 1 = r = 2 ∑ 1 0 ( r 2 − 1 ) = 3 7 5